Marine Biologically Active Compounds as Feed Additives - Michalak, Izabela (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue presents high-quality research papers as well as review articles addressing recent advances in the use of marine bioactives in animal nutrition. The marine environment constitutes a relatively untapped source of biologically active compounds that can be applied in various areas, such as improvement of animal performance, health maintenance, and disease prevention. Numerous marine-based compounds isolated from marine organisms (especially seaweeds) have diverse biological activities, including antioxidative, anti-inflammatory, antibacterial, antifungal, and antiviral activities that can be beneficial to animal health. Additionally, the application of marine bioactives as feed additives can increase the nutritional value of products of animal origin. In this Special Issue, the main attention was focused on seaweeds and their application in poultry (laying hen and broiler chickens) and pig feed. The suitable processing of marine resources required for their optimal use as feed/feed additives was underlined. The contained publications present scientific evidence for the use of various seaweeds as feed additives that improve health (enhanced immunity, prebiotic effect), growth performance, and production. Inclusion of this unconventional material in animal nutrition can enrich products with active compounds, such as micro- and macroelements, polyunsaturated fatty acids, and pigments which are beneficial for consumers.